Building a Network of Health Professionals for Breast and Cervical Cancer Control in the Andean Region - Diana Mendoza-Cervantes; Isabel Otero; Jo Anne Zujewski; Jorge Ferrandiz Salazar; Gabriela López Córdova; Cathy Muha; Lisa Stevens (Journal of Global Oncology, 2017)
Purpose: Cancer mortality is approximately twice as high in Latin American countries than in more developed countries. In particular, the countries of the high Andean region of Latin America carry a double burden of breast and cervical cancers. In these countries, there are disproportionately higher mortality to incidence ratios compared with other regions in Latin America. The US National Cancer Institute’s Center for Global Health, the Pan American Health Organization, and the Ministry of Health in Peru collaborated to design and execute an education and advocacy workshop in Lima, Peru. The workshop was convened to discuss regional challenges and practices, as well as to support the implementation of Plan Esperanza, Peru’s national cancer control plan. Methods: Workshop participants included local and international experts to present the state of the science, health practitioners, and advocacy groups to discuss unique barriers that women in the region experience. Results: Inequalities in access to and distribution of medical expertise, lack of continuity of cancer control plans, and the need for sustained public buy-in emerged as obstacles. Conclusion: The workshop provided a forum to discuss key issues regarding breast and cervical cancer control among health professionals and advocates in Peru and the region. This article outlines the resulting recommendations.